If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(2x + -3) = 12x + 5 Reorder the terms: 5(-3 + 2x) = 12x + 5 (-3 * 5 + 2x * 5) = 12x + 5 (-15 + 10x) = 12x + 5 Reorder the terms: -15 + 10x = 5 + 12x Solving -15 + 10x = 5 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. -15 + 10x + -12x = 5 + 12x + -12x Combine like terms: 10x + -12x = -2x -15 + -2x = 5 + 12x + -12x Combine like terms: 12x + -12x = 0 -15 + -2x = 5 + 0 -15 + -2x = 5 Add '15' to each side of the equation. -15 + 15 + -2x = 5 + 15 Combine like terms: -15 + 15 = 0 0 + -2x = 5 + 15 -2x = 5 + 15 Combine like terms: 5 + 15 = 20 -2x = 20 Divide each side by '-2'. x = -10 Simplifying x = -10
| S^2-2s+10=0 | | 2t^2=2t+1 | | x^2+15X-7=0 | | 2(n+12)=2(n+9)+6 | | 2(n+11)=2(n+9)+6 | | y=x^2-2x-6 | | y=x+2-x^2 | | -2(2n+1)=4 | | 2x^2+3=-4x | | 0.2(30-10x)=0.6(4x+2) | | 6(p-1)=3p | | -4x+15=11 | | 7x-5=7x+5 | | -4x+7=-1 | | z^2+12x+31=0 | | 5x^2=36x+32 | | 6(4z-1)-4(z+2)=17(z+1) | | 4y+y=6 | | c+5= | | .00000000000112=4x^3+5.6x^2 | | (x-1)(x+2)= | | (x+4)(x+1)= | | 15x+12y=0 | | 8=D | | 2x/5=-3+7 | | 4z^2+32z+63=0 | | 9n+72= | | 14y^2-15y+4=0 | | 3h=2h-8 | | 6(a+2)= | | 0.28x-0.75x=-13 | | 49s^2-9=0 |